1996
DOI: 10.2136/sssaj1996.03615995006000050024x
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of Nitrogen from Slow‐Release Urea Sources in Sandy Soils

Abstract: Application of readily soluble forms of N fertilizers to sandy soils may cause leaching of NO3‐N resulting in contamination of groundwater. The leaching loss of N may be reduced to some extent by using slow‐release forms of N. An intermittent leaching and incubation technique, to mimic natural occurrence of rainfall and dry conditions, was used to examine the leaching of N from readily soluble (NH4NO3) and slow‐release fertilizers [isobutylidene diurea (IBDU) and a polyolefin resin‐coated urea, Meister] in Wab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(78 citation statements)
references
References 0 publications
3
71
0
4
Order By: Relevance
“…An increasing use of nitrogenous fertilizers and their subsequent leaching as nitrate from the rootzone of cropping systems is recognised as a potential source of groundwater contamination, because the harvested crop seldom takes up more than 25-70% of the total applied fertilizer (Allison, 1996). Several researchers have reported substantial leaching (6-45%) of applied N under citrus cultivation in field conditions (Wang and Alva, 1996;Paramasivam et al, 2002;Sluggett, 2010). Similarly, in lysimeter experiments, Boaretto et al (2010) showed 36% recovery of applied nitrogen by orange trees, while Jiang and Xia (2008) reported N leaching of 70% of the initial N value, and found denitrification and leaching to be the main processes for the loss of N. These studies suggest that knowledge of the nitrogen balance in cropping systems is essential for designing and managing drip irrigation systems and achieving high efficiency of N fertilizer use, thereby limiting the export of this nutrient as a pollutant to downstream water systems.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing use of nitrogenous fertilizers and their subsequent leaching as nitrate from the rootzone of cropping systems is recognised as a potential source of groundwater contamination, because the harvested crop seldom takes up more than 25-70% of the total applied fertilizer (Allison, 1996). Several researchers have reported substantial leaching (6-45%) of applied N under citrus cultivation in field conditions (Wang and Alva, 1996;Paramasivam et al, 2002;Sluggett, 2010). Similarly, in lysimeter experiments, Boaretto et al (2010) showed 36% recovery of applied nitrogen by orange trees, while Jiang and Xia (2008) reported N leaching of 70% of the initial N value, and found denitrification and leaching to be the main processes for the loss of N. These studies suggest that knowledge of the nitrogen balance in cropping systems is essential for designing and managing drip irrigation systems and achieving high efficiency of N fertilizer use, thereby limiting the export of this nutrient as a pollutant to downstream water systems.…”
Section: Introductionmentioning
confidence: 99%
“…The NH 4 + -N release pattern from www.intechopen.com some CRFs was similar to those of the soluble fertilizers and closely desirable for vegetable production. Many researches have demonstrated that CRFs and SRFs can reduce N, particularly NO 3 --N leaching on sandy soils compared with soluble fertilizers (Alva, 1992;Wang & Alva, 1996;Paramasivam & Alva, 1997;Fan & Li, 2009). Moreover, not only NO 3 --N but also other nutrients such as P, K, calcium (Ca), magnesium (Mg), and copper (Cu) can CRFs reduce leaching compared with uncoated fertilizers.…”
Section: Nutrient Availability From Controlled-and Slow-release Fertimentioning
confidence: 99%
“…Quando o SFT foi aplicado junto com a uréia, a percolação de amônio iniciou-se a partir da sexta adição de água e atingiu o máximo, de aproximadamente 50 mg L -1 , na nona percolação (Figura 2); na ausência de SFT, a percolação iniciou-se na décima primeira adição de água e foi aumentando gradativamente até a última percolação, atingindo a concentração máxima de aproximadamente 10 mg L -1 (Figura 2). Nos tratamentos com sulfato mais SFT, a percolação de amônio iniciou-se na quinta percolação e atingiu o máximo de 60 mg L -1 , na décima primeira percolação; na ausên-cia do fosfato, as perdas somente começaram na déci- (Wang & Alva, 1996). À medida que a nitrificação do amônio na solução do solo prossegue, a atividade do amônio na solução diminui e parte da fração retida nas cargas negativas migra para a fase líquida, podendo ser percolada.…”
Section: Percolação De Amôniounclassified
“…A concentração de nitrato nas amostras de solo coletadas ao término do experimento não diferiu daquela observada no tratamento que não recebeu N, tanto na presença quanto na ausência de SFT (Figura 3). Wang & Alva (1996) também observaram que praticamente todo o nitrato aplicado a solos arenosos foi lixiviado nas primeiras percolações de água, em experimento com colunas de lixiviação, num método similar ao do presente estudo. Em solos de regiões com altas precipitações pluviométricas deve-se, portanto, evitar a adição de fertilizantes nítricos.…”
Section: Percolação De Nitratounclassified
See 1 more Smart Citation